Dolor a la aplicación anestésica con anestesia convencional y anestesia digital en estudiantes de la Facultad de Odontología, Universidad Nacional de la Amazonía Peruana, según sexo, 2024 - Reategui Echevarria, Franco Andre (2024)
The main objective of this research was to determine whether there is a relationship between the intensity of pain during anesthetic application with conventional anesthesia and digital anesthesia in students of the Faculty of Dentistry, National University of the Peruvian Amazon, according to sex, 2024. Using a quantitative approach, descriptive and explanatory level with an experimental design; made up of a population of 42 students, the Visual Analogue Scale (EVA) was used. The results revealed that, regarding the intensity of pain during anesthetic application with digital anesthesia in the reservoir, 73.8% of students experienced mild pain, on the contrary, with conventional anesthesia, 50.0% felt moderate pain and 2.4% felt severe pain. In short, it has been shown that the difference in means of the levels of pain intensity upon puncture and deposit of the anesthetic were determined to be significant, considering that digital anesthesia generates less pain than conventional anesthesia. When performing statistical tests to determine whether there is a relationship between the application of both conventional and digital anesthesia and sex, we concluded that in the case of conventional anesthesia (puncture), the result is not significant (p = 0.491, > 0.05), in the case of conventional anesthesia (deposit) the result is not significant (p = 0.620, > 0.05). On the other hand, in the case of digital anesthesia (puncture) the result is significant (p = 0.031, < 0.05), Finally, in the case of digital anesthesia (deposit) the result is not significant (p = 0.216, > 0.05).